A novel interventional guidance framework for transseptal puncture in left atrial interventions - Morais, Pedro André Gonçalves (2018)
Access to the left atrium is required for several percutaneous cardiac interventions. In these procedures, the inter-atrial septal wall is punctured using a catheter inserted in the right atrium via the venous system under image guidance. Although this approach (termed transseptal puncture - TSP) is performed daily, complications are common. Moreover, the exact location at which the septum needs to be traversed is determined entirely based on the interventionist’s experience, which is sub-optimal. In this work, we present a novel concept for the development of an interventional guidance framework for TSP. The pre-procedural planning stage is fused with 3D intra-procedural images (echocardiography) using manually defined landmarks, transferring the relevant anatomical landmarks to the interventional space and enhancing the echocardiographic images. In addition, electromagnetic sensors are attached to the surgical instruments, tracking them and allowing the inclusion of their spatial position in the enhanced intra-procedural world. Two patient-specific atrial phantom models were used to evaluate this framework. One operator performed the planning, calibrated the setup and performed the puncture. To assess the framework’s accuracy, a metallic landmark was positioned in the punctured location and compared with the ideal one. The intervention was possible in both models, but in one case positioning of the landmark failed. An error of approximately of 6 mm was registered for the successful case. Technical characteristics of the framework showed an acceptable performance, with a frame rate ~5 frames/sec. The manual calibration setup required ~60 min. This study presented a proof-of-concept for an interventional guidance framework for TSP. However, a more automated solution and further studies to assess its accuracy are required.